HYDROGEOLOGIC CHARACTERISTICS OF THE ALLUVIAL TUFF AQUIFER OF NORTHERN SAHAND MOUNTAIN SLOPES, TABRIZ, IRAN - Asghari Moghaddam A.; Allaf Najib M. (My University, 2006)
The Tabriz area is a densely populated area of northwestern Iran (more than 1.5 million in population) with a large proportion of its drinking, domestic, industrial and agricultural water supplied from groundwater resources. The average rate of drinking and industrial water use in the city of Tabriz is about 3.45 m3 s–1. The Plio-Pleistocene unconfined alluvial tuff aquifer (about 1,275 km2), the most important aquifer in the area, has been known for many years as a reliable resource. The greatest estimated thickness of the alluvial tuff lies in the Saidabad area, with 350 m thickness. There are 994 deep and 284 shallow active pumping wells and 83 qanats operate in the alluvial tuff aquifer. The total water withdrawal from all these artificial discharge points has been measured at 72, 3.8 and 17 million m3/year, respectively. Analytical and numerical methods have been applied to the constant rate pumping test data from the Saidabad wellfield (eight pumping and three observation wells). The values of electrical conductivity in the groundwater of alluvial tuff aquifer range from 203 to 960 μS cm–1 and bicarbonate type water dominates.
Keywords: ALLUVIAL TUFF AQUIFER; ANALYTICAL SOLUTIONS; NUMERICAL SOLUTIONS; TABRIZ (IRAN); OVER-ABSTRACTION; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен